SOME PROPERTIES OF SUBSEMIHYPERGROUPS - Ari wardayani; Mitha Cerinda; Idha Sihwaningrum; Mutia nur Estri; Wuryatmo Ahmad Sidik (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2021)
In this paper we will present two properties of subsemihypergroups. The first property is a relation between subsemihypergroups and semihypergroup. This property enable us to get the second property, which provides a relation between subsemihypergroups and regular semihypergroups.